BRAND IMAGE RELATIONSHIP, MERCHANDISE, AND ATMOSPHERE STORE WITH THE INTEREST OF BUYING A BRAND WAREHOUSE AT SOGO GALAXY MALL SURABAYA - Putu Imam Kristianto; Sengguruh Nilowardono (NAROTAMA UNIVERSITY, Indonesia, 2019)
This research is motivated by a decrease in the sales volume of the famous women's clothing. Warehouse located at Sogo Galaxi Mall Surabaya, the selling rights are owned by PT. Mitra Adiperkasa Tbk. From the data obtained from the women's clothing products, Warehouse Sogo Galaxi Mall Surabaya, in their sales from 2011 to 2015, their sales figures have always decreased. This has a direct impact on declining company revenue in line with the decline in sales volume of the Warehouse women's clothing. If this decline continues, it is feared that the company's performance will go out of business. In particular, the researchers chose the Warehouse women's clothing products whose sales for the Surabaya area are owned by PT. Mitra Adiperkasa Tbk. This study aims to determine the relationship between brand image, merchandise, and store atmosphere with buying interest in women's clothing products Warehouse at Sogo Galaxi Mall Surabaya. In this study, data was collected by distributing questionnaires to 75 respondents, which aims to determine the respondents' responses to each variable. The analysis used includes a validity test, reliability test, Spearman's rank correlation analysis, and t-test. From the results of the analysis using Spearman's rank correlation, it can be seen that the variables Brand Image, Merchandise, and Store Atmosphere all have a moderate and significant relationship with Purchase Interest in Warehouse women's clothing products. With the sequential results of the variables related to Purchase Interest is a Store Atmosphere of (0.558), Merchandise (0.551), and a Brand Image of (0.461)